VIGILANTISME DALAM NOVEL “TANAH PARA BANDIT” KARYA TERE LIYE: TINJAUAN PSIKOLOGI KRIMINAL - Labibah, Jihan (Universitas Negeri Surabaya, 2024)
Vigilantism, as a phenomenon of law enforcement carried out by non-authoritative individuals or groups independently, has attracted attention in the study of criminal psychology. This article analyzes the novel Tanah Para Bandit by Tere Liye, which explores the dynamics of power, corruption, and crime in the society of Indonesia's capital city. The novel shows power corruption is rampant in various walks of life, while vigilantism emerges as a form of resistance to injustice. However, these vigilante actions are often extrajudicial, creating a spiral of violence and uncertainty, and raising questions about accountability and fair law enforcement. The research method uses a descriptive qualitative approach with content analysis, identifying the dominant themes and dynamics of power, corruption, and crime in the novel. The results highlight the moral conflict behind vigilantism, as well as its social impact in the context of a corrupt society.